A forensic evaluation of plague – a re-emerging infectious disease with biowarfare potential. (July 2020) - Byard, Roger W.
Plague is an acute infectious disease caused by the gram-negative cocco-bacillus Yersinia pestis . It has been responsible for 200 million deaths throughout history with three major pandemics. There are three forms: bubonic, septicaemic and pneumonic, each carrying a significant mortality rate. The usual transmission is from fleas carried by rodents. Recently, it has been listed as one of the reemerging infectious diseases globally, with a potential use in bioterrorism. At autopsy there may be lymphadenopathy, fulminant pneumonia or diffuse interstitial pneumonitis. However any organ may be affected with myocarditis, meningitis, pharyngitis and hepatic and splenic necrosis. The lethality of plague with the resurgence in numbers of cases, development of antibiotic resistance, recent occurrence in urban areas and the lack of a vaccine make it a disease not to be missed in the mortuary.